COVID-19 and the impact of the pandemic on the mental health of physical therapy professionals: an integrative review (Research, Society and Development, 2021)
Amid a pandemic that was detected in the world at the end of 2019, as a global outbreak of unknown history in which it is approved by the common picture of fatigue, cough, high fever and especially respiratory distress in all patients, and currently diagnosed as Coronavirus 2019 (COVID-19). The guiding question: What are the impacts on the mental health of physical therapy professionals during a COVID-19 pandemic? Therefore, the general objective that guided the research was: To analyze the scientific evidence on the impact on the psychological of physical therapy professionals during the COVID-19 pandemic. This is a systematic review, which is a review method that performs many functions criticisms; they can provide summaries of the state of knowledge in a field, from which future research priorities can be identified; in addition to identifying problems in primary research to be corrected in future studies; and generate or evaluate theories about how or why phenomena occur.